Prognostic factors for disease relapse in patients with neuroendocrine tumours who underwent curative surgery. (September 2016) - Slagter, A.E.; Ryder, D.; Chakrabarty, B.; Lamarca, A.; Hubner, R.A.; Mansoor, W.; O'Reilly, D.A.; Fulford, P.E.; Klümpen, H.J.; Valle, J.W.; McNamara, M.G.
Abstract: Aim: Surgery is the only modality of cure in patients diagnosed with neuroendocrine tumours (NETs). The aim of this study was to identify prognostic factors associated with disease relapse in patients with NETs treated by potentially-curative surgery. Methods: Sequential patients registered in The Christie European NET Society (ENETS) Centre of Excellence, with grade (G)1 or G2 NETs who had undergone curative surgery (February 2002–June 2014) were included. Investigated prognostic factors for relapse were: age, gender, TNM stage, tumour-localisation, functionality, genetic predisposition, presence of multiple NETs, second malignancy, grade (Ki-67-based), presence of vascular and/or perineural invasion, necrosis, surgical margin (R0/R1), Eastern Cooperative Oncology Group performance status and Adult Comorbidity Evaluation co-morbidity score. Results: One hundred and eighty-eight patients were identified [median age of 60 years (range 16–89)]. With a median follow-up of 2.6 years, 43 relapses occurred. The estimated median relapse-free survival (RFS) for the entire cohort was 8.0 years (95% confidence interval [CI] 5.9–10.0 years). In univariate analysis, primary NET location (p = 0.01), ENETS T-(HR-1.4; 95%-CI 1.0–2.0, p = 0.026), N-(HR-2.0, 95%-CI 1.1–3.9, p = 0.026) and M-stage (HR-2.6, 95%-CI 1.1–6.3, p = 0.052), grade (Ki-67%-based) (HR-2.5; 95%-CI 1.4–4.7; p = 0.003) and perineural invasion (HR-2.1; 95%-CI 1.1–3.9; p = 0.029) were prognostic for relapse. Factors remaining significant after multivariable analysis were tumour size (HR-1.67; 95%-CI 1.04–2.70; p = 0.03), nodal involvement (HR-2.61; 95%-CI 1.17–5.83; p = 0.013) and Ki-67 at the time of diagnosis (HR-1.93; 95%-CI 1.24–3.0; p = 0.002). Conclusion: Size of tumour, lymph node involvement and Ki-67 were independent prognostic factors for relapse after potentially curative surgery in NET.